Electron beam induced current microscopy investigation of GaN nanowire arrays grown on Si substrates. (15th November 2016) - Neplokh, Vladimir; Ali, Ahmed; Julien, François H.; Foldyna, Martin; Mukhin, Ivan; Cirlin, George; Harmand, Jean-Christophe; Gogneau, Noëlle; Tchernycheva, Maria
Abstract: We report on the electron beam induced current (EBIC) investigation of GaN nanowires grown on n-doped Si (111) substrates. The objective of this study is to acquire information about the modifications of the substrate properties induced by the wire growth. We show that the growth procedure using deposition of an ultra-thin AlN layer prior to the nanowire growth step leads to the formation of a p-n junction in the Si substrate with a high surface conductivity. The induced p-n junction exhibits a photoresponse over the spectral range from 360 nm to 1100 nm. The properties of the induced p-n junction are investigated on the cross section and in a top view configuration with EBIC microscopy. For a localized contact of the GaN nanowires, the collection range in Si extends over a few millimeters. The treatment of the surface using reactive ion etching with a CHF3 plasma leads to the inhibition of the surface conductivity and to the appearance of an S-shape in the current-voltage characteristics under illumination. The conversion efficiency of the plasma-treated sample under AM1.5G solar spectrum is estimated to be in the 2.1–2.7% range.